Auctions with variable supply and competing auctioneers - Damianov, Damian (2005)
The dissertation studies game theoretical models of competitive bidding on multi-unit auction markets. The analysis concerns both monopoly and oligopoly settings. A major part of the thesis deals with equilibrium bidding in variable supply auctions trade mechanisms in which a monopoly seller determines supply in view of the received bids. These trade mechanisms are used in a variety of economic contexts, e.g. financial markets for Treasury bills and Initial Public Offerings. The final part of the thesis presents a model in which several sellers design trade mechanisms in order to attract buyers. The analysis derives the equilibrium trade mechanism in this oligopoly market. The presented models strengthen our understanding of the micro-mechanisms of price formation and their role in shaping market outcomes.